Efeito do Treinamento Corretivo Postural (TCP®) sobre a glicemia de jejum, hemoglobina glicada e cortisol em mulheres diabéticas de 44 a 55 anos - Wenzel, Isabel Cristina (2014)
It is well established in the literature that the type 2 diabetes mellitus (T2DM) may be related to physical inactivity, high fat diet, stress, weight gain, in addition to advanced age. Consequently, some studies show that the search for a better quality of life through exercise and balanced diets are increasing beyond the control of metabolic markers related to diabetes, preventing complications of the disease and excess free radicals. The aim of this study was to determine the effect of TCP® in people with T2DM, associated to the diet, in a targeted manner, evaluating: lipid profile, uric acid, fasting glucose, glycated hemoglobin and cortisol. We selected 21 women between 44-55 years old, that were divided into four groups: diabetic sedentary (SD); diabetic exercised (ED); exercised normal (EN); and normal sedentary (NS). Was used as the intervention TCP® with a frequency of 3 times/week, 1 hour per day, at 20 weeks, which was monitored throughout the study period, associated to the the diet. Blood samples were collected pre and post intervention, to perform the measurements of cholesterol, triglycerides, HDL, uric acid, glucose, cortisol, and glycated hemoglobin. Compared are the results before (b) and after (a) was used: - non-parametric Wilcoxon and Friedman; and - delta (%), which was used to determine the intra-individual variation uniformly. Results: There were no significant differences in the variables analyzed in this study, except glycated hemoglobin in the ED group, which showed a statistically significant difference (p <0.05). In intragroup comparison, when using the percentage delta, major clinical changes were obtained mainly in the exercised groups, considering that many of the values found returned to normal reference values. Final considerations: the protocol TCP® method associated with the diet was effective in improving the parameters analyzed evidence, making important clinical changes in diabetics who exercised. Examples of this were the clinical changes, with statistical difference in plasma levels of glycated hemoglobin in the ED, important for the prevention of complications of the disease factor.